Metastable Ni(I)-TiO2-x Photocatalysts: Self-Amplifying H2 Evolution from Plain Water without Noble Metal Co-Catalyst and Sacrificial Agent - Altomare, Marco; Qin, Shanshan; Saveleva, Viktoriia A.; Badura, Zdenek; Tomanec, Ondrej; Mazare, Anca Valentina; Zoppellaro, Giorgio; Vertova, Alberto; Taglietti, Angelo; Minguzzi, Alessandro; Ghigna, Paolo; Schmuki, Patrik (Journal of the American Chemical Society, 2023)
Decoration of semiconductor photocatalysts with cocatalysts is generally done by a step-by-step assembly process. Here, we describe the self-assembling and self-activating nature of a photocatalytic system that forms under illumination of reduced anatase TiO2 nanoparticles in an aqueous Ni2+ solution. UV illumination creates in situ a Ni+/TiO2/Ti3+ photocatalyst that self-activates and, over time, produces H2 at a higher rate. In situ X-ray absorption spectroscopy and electron paramagnetic resonance spectroscopy show that key to self-assembly and self-activation is the light-induced formation of defects in the semiconductor, which enables the formation of monovalent nickel (Ni+) surface states. Metallic nickel states, i.e., Ni0, do not form under the dark (resting state) or under illumination (active state). Once the catalyst is assembled, the Ni+ surface states act as electron relay for electron transfer to form H2 from water, in the absence of sacrificial species or noble metal cocatalysts.
CRIS-Team Scopus Importer:2023-12-15